A Comprehensive Review on Bigels as a Potential Replacement to Solid Fat in Food Applications - Wasiya Farzana; Sneha Mahesh; Sachin Sharma; Irshaan Syed; Gholamreza Abdi; Rituja Upadhyay (Journal of Food Quality)
Bigels, composed of hydrogels and oleogels, are emerging as innovative materials with significant potential in the food industry. This review explores the application of bigels in various food contexts, including conventional and novel meats, plant-based alternatives, baked foods, 3D printing, and advanced packaging technologies. In traditional meat products, bigels have demonstrated their ability to replace up to 50% of animal fat, maintaining acceptable sensory and physical properties. Bigels are used in novel meat formulations to enhance nutritional profiles by reducing sodium, saturated fats, and synthetic additives, while providing improved stability and texture as effective fat substitutes. Additionally, bigels are utilized in 3D food printing for personalized nutrition and innovative designs, offering improved stability and structural integrity during printing process over traditional gels. Bigels are being explored in advanced packaging as coatings to delay oxidation and prevent dehydration in seafood, and in intelligent packaging that responds to food freshness, showcasing their potential to extend shelf life and reduce food waste. Despite their advantages, the use of bigels in the food industry faces challenges including ingredient safety, regulatory compliance, and consumer acceptance. The integration of bigels into food products requires careful consideration of their physicochemical properties and interactions with other ingredients. Future research is needed to optimize bigel formulations, improve their stability under processing conditions, and address consumer preferences. Overall, bigels present a promising solution for developing healthier, more sustainable food products with the potential to revolutionize the industry by enhancing food’s nutritional profile and sensory qualities. Continued research and innovation are crucial for overcoming existing challenges and fully realizing the benefits of bigels in the global food market.